Trade openness, institutions and economic growth in Sub-Saharan Africa - Taiwo AKINLO; Charles Olalekan OKUNLOLA (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This research investigates the interactive effect of trade openness and the institutional quality on economic growth in sub-Sahara Africa. The sample consists of 38 sub-Saharan African countries and covers the period 1986-2015. Pooled OLS, fixed effect, and Dynamic GMM were used as estimation techniques. The empirical section used a nonlinear growth regression specification that interacts trade openness with law and order, bureaucratic quality, corruption, government stability, and democratic accountability. The study found that corruption, government stability, law and order, and bureaucratic quality as institutional quality variables harm economic growth. The interaction of trade openness and institutional quality variables positively impacted economic growth. It is an indication that trade openness better impacted economic growth in the presence of high-quality institutional variables.